Dysregulation of Kisspeptin and Leptin, as Anorexigenic Agents, Plays Role in the Development of Obesity in Postmenopausal Women - Andon Hestiantoro; Brilliant P. K. Astuti; Raden Muharam; Gita Pratama; Fiastuti Witjaksono; Budi Wiweko (International Journal of Endocrinology)
During the menopausal period, women have a higher tendency to develop obesity and any other metabolic syndromes. Dysregulation of leptin and kisspeptin signaling as anorexigenic agents is believed to be the connection between metabolic disorders and altered reproductive function. Therefore, this study aimed at investigating the association between leptin, soluble leptin receptor (sOBR), free leptin index, kisspeptin concentrations, and body mass index (BMI) in postmenopausal women. A cross-sectional study was carried out among 171 postmenopausal women aged 40–75 years from 2017 to 2018. Subjects were assigned into 2 groups according to their BMIs: obese group (84 subjects) and nonobese group (87 subjects). In addition to anthropometric measurement, blood sample was collected from each subject for leptin, sOBR, free leptin index (FLI), and kisspeptin evaluation. Bivariate and correlation analysis discovered that leptin and FLI were positively correlated with BMI, while sOBR and kisspeptin were negatively correlated with BMI. Among those variables, multivariate analysis found that leptin, sOBR, and kisspeptin were independently associated with obesity. Therefore, it can be concluded that higher serum leptin concentration and FLI, as well as lower serum sOBR and kisspeptin concentrations, are significantly associated with obesity in postmenopausal women.